2018
DOI: 10.9778/cmajo.20180044
|View full text |Cite
|
Sign up to set email alerts
|

Canadian federal penitentiaries as obesogenic environments: a retrospective cohort study

Abstract: The Canadian correctional environment can be considered obesogenic, with most inmates experiencing undesirable and rapid weight gain during their incarceration. Rates of obesity increased dramatically during incarceration, and could put inmates at increased risk of obesity-related health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…In our recent publication, we found that Canadian inmates gained a significant amount of weight during incarceration 25. Our findings showed that, on admission, obesity rates were similar to the general Canadian population (~27%), but after at least 6 months of incarceration obesity rates increased to 45% for the inmate population 25. We suspect the observed weight gain was associated with tobacco cessation in Canadian inmates.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…In our recent publication, we found that Canadian inmates gained a significant amount of weight during incarceration 25. Our findings showed that, on admission, obesity rates were similar to the general Canadian population (~27%), but after at least 6 months of incarceration obesity rates increased to 45% for the inmate population 25. We suspect the observed weight gain was associated with tobacco cessation in Canadian inmates.…”
Section: Introductionsupporting
confidence: 49%
“…The majority of studies on obesity in prison were out of Australia, the USA and the UK 26. In our recent publication, we found that Canadian inmates gained a significant amount of weight during incarceration 25. Our findings showed that, on admission, obesity rates were similar to the general Canadian population (~27%), but after at least 6 months of incarceration obesity rates increased to 45% for the inmate population 25.…”
Section: Introductionmentioning
confidence: 46%
See 1 more Smart Citation
“…The observed weight gain is considered to be unhealthy since it significantly increased obesity prevalence during incarceration, with obesity rates rising from 27% at admission to the penitentiaries to 46% at the time of follow-up ( Johnson et al, 2018). This represented a 70% increase during incarceration ( Johnson et al, 2018). We suspected that weight gain could be associated with mental health and psychotropic medication use.…”
Section: Introductionmentioning
confidence: 94%
“…A recent study found weight gain in Canadian federal penitentiaries to be worrisome, since 73% of people gained weight during incarceration ( Johnson et al, 2018). The observed weight gain is considered to be unhealthy since it significantly increased obesity prevalence during incarceration, with obesity rates rising from 27% at admission to the penitentiaries to 46% at the time of follow-up ( Johnson et al, 2018). This represented a 70% increase during incarceration ( Johnson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%